2013
DOI: 10.3389/fnint.2013.00032
|View full text |Cite
|
Sign up to set email alerts
|

Autism: the micro-movement perspective

Abstract: The current assessment of behaviors in the inventories to diagnose autism spectrum disorders (ASD) focus on observation and discrete categorizations. Behaviors require movements, yet measurements of physical movements are seldom included. Their inclusion however, could provide an objective characterization of behavior to help unveil interactions between the peripheral and the central nervous systems (CNSs). Such interactions are critical for the development and maintenance of spontaneous autonomy, self-regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
293
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(310 citation statements)
references
References 91 publications
14
293
2
1
Order By: Relevance
“…Again, the expectation about the variability itself needs to be acquired across multiple fluctuations (experiences), to allow for proper learning and reshaping of priors. In a meticulous individuallevel study on micro-movements, Torres et al (2013) showed that, in action as well, subjects with ASD did not properly learn about the variability or unreliability intrinsic in their own motions, making their micro-movements more random or ''memory-less". Even though they were able to perform according to the goals of the motor task, Brincker and Torres (2013, p. 2) observed that ''the movement variability from experiencing the ''here and now" seemed to be the only useful kinesthetic information to them".…”
Section: Robustness In Perception and Actionmentioning
confidence: 99%
“…Again, the expectation about the variability itself needs to be acquired across multiple fluctuations (experiences), to allow for proper learning and reshaping of priors. In a meticulous individuallevel study on micro-movements, Torres et al (2013) showed that, in action as well, subjects with ASD did not properly learn about the variability or unreliability intrinsic in their own motions, making their micro-movements more random or ''memory-less". Even though they were able to perform according to the goals of the motor task, Brincker and Torres (2013, p. 2) observed that ''the movement variability from experiencing the ''here and now" seemed to be the only useful kinesthetic information to them".…”
Section: Robustness In Perception and Actionmentioning
confidence: 99%
“…In autism spectrum disorder (ASD), for example, infants who are later diagnosed with autism display sensorimotor problems (e.g., postural stability, gait, timing and coordination of motor sequences, anticipatory adjustments and face expression) before they reach the developmental age associated with theory of mind, when typically developing children engage in joint attention and joint action with others and are learning to communicate (Trevarthen and Delafi eldButt 2013;Gallese et al 2013;Cattaneo et al 2007;Cook et al 2013;Gallagher 2004;Hilton et al 2012;Fabbri-Destro et al 2009;Whyatt and Craig 2013;David et al 2014). In individuals with ASD, Torres and colleagues show the occurrence of disrupted patterns in re-entrant (afferent, proprioceptive) sensory feedback that usually contributes to the autonomous regulation and coordination of motor output, and supports volitional control and fl uid, fl exible transitions between intentional and spontaneous behaviors (Torres 2013;Torres et al 2013). In ASD, as well as in other developmental disorders (e.g., Down Syndrome), disruptions in motor processes may partly explain why individuals show diffi culties in distinguishing goal-directed from goal-less movement (Torres 2013;Brincker and Torres 2013), anticipating the consequences of their own impending movements and applying fi ne-tuned discriminations to the actions and emotional facial expressions of others during real-time social interactions.…”
Section: Enactive Approaches To Developmental Disordersmentioning
confidence: 99%
“…This point is salient in light of the recent discovery of a possible ontogenetically primary movement disruption in children with autism spectrum disorder (Anzeluwicz, Sobota, & Delafield‐Butt, 2016; Fournier, Hass, Naik, Lodha, & Cauraugh, 2010; Teitelbaum, Teitelbaum, Nye, Fryman, & Maurer, 1998; Torres et al., 2013). Sensorimotor timing and integration of single action units appears to be fundamentally disrupted in children with autism spectrum disorder, which some authors have posited can explain consequential difficulties of engagement and learning by thwarting a basic motor intention and leading to frustration, distress and social withdrawal (Cook, 2016; Trevarthen & Delafield‐Butt, 2013; Whyatt & Craig, 2013).…”
Section: Discussionmentioning
confidence: 99%